2004
DOI: 10.1111/j.1523-1755.2004.00518.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis and risk factors for idiopathic membranous nephropathy with nephrotic syndrome in Japan

Abstract: IMN is a disease with a comparatively good prognosis in Japan even when it is associated with nephrotic syndrome. Steroid therapy, which has not been recommended for IMN in most review articles, seems to be useful at least for Japanese patients. In particular, a remission from heavy proteinuria likely results in a favorable outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
148
2
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 161 publications
(168 citation statements)
references
References 13 publications
(22 reference statements)
13
148
2
5
Order By: Relevance
“…The renal survival rate was 60 % at 20 years after diagnosis in patients with primary MN, and the renal survival rate in patients on steroid therapy was significantly higher in patients on supportive therapy alone in Japan [16], while spontaneous remission was reported to be common (32 %) in patients with primary MN with nephrotic syndrome in Spain [17], even in patients exhibiting chronic renal impairment [18]. Whether treatment with renin-angiotensin blockers or immunoglobulins other than steroids has a favorable effect on the renal prognosis of primary MN should be elucidated in future clinical studies.…”
Section: Discussion and Commentsmentioning
confidence: 95%
See 1 more Smart Citation
“…The renal survival rate was 60 % at 20 years after diagnosis in patients with primary MN, and the renal survival rate in patients on steroid therapy was significantly higher in patients on supportive therapy alone in Japan [16], while spontaneous remission was reported to be common (32 %) in patients with primary MN with nephrotic syndrome in Spain [17], even in patients exhibiting chronic renal impairment [18]. Whether treatment with renin-angiotensin blockers or immunoglobulins other than steroids has a favorable effect on the renal prognosis of primary MN should be elucidated in future clinical studies.…”
Section: Discussion and Commentsmentioning
confidence: 95%
“…Since MCNS develops in patients at younger ages [5,15] while primary MN develops in a relatively elderly population [15,16], the frequency of these diseases may depend on the distribution of the age ranges of patients registered in each year. Indeed, the rate of native biopsies of subjects younger than 20 years of age slightly increased from 11.4 % in 2009 to 12.7 % in 2010 (Table 3) and the mean age of patients with nephrotic syndrome slightly decreased from 53.5 years in 2009 to 50.1 years in 2010 (Table 5) in the J-RBR.…”
Section: Discussion and Commentsmentioning
confidence: 99%
“…Prednisolone, either alone or combined with an immunosuppressive drug, seems to be useful in Japanese patients. Indeed, steroid therapy is effective not only in inducing a remission of nephrotic syndrome but also in preserving renal function [4]. However, Hogan et al [5] demonstrated a lower 5-year renal survival rate in the steroid/no-therapy group than in patients receiving the steroid and alkylating agents.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrates enhanced staining of PLA2R in glomeruli in cases with idiopathic MGN compared with negative staining in secondary MGN [9]. On the other hand, secondary MGN accounts for about 10-20 % of MGN, and causative antigens reported were drugs, tumor associated antigens such as CEA and cytokeratin 19 fragment, Hepatitis B virus, envelope antigen, and the other antigens in autoimmune diseases [6,7]. In the present case, three possible causes of MGN were considered; coincidence of idiopathic MGN, MGN associated with pulmonary adenocarcinoma or gefitinib treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The deposition of IgA and C3 was also found mainly in the mesangial areas. The expression of phospholipase A2 receptor (PLA2R), which is considered as the antigen of primary MGN [6,7], did not enhance in glomeruli, although it was enhanced on glomerular capillaries in some cases of primary MGN (data not shown). As electron microscopic findings, granular electron dense deposit was found irregularly at the subepithelial region on the glomerular basement membrane (GBM) (Fig.…”
Section: Case Reportmentioning
confidence: 96%